Analisis Konten Visual pada Akun Instagram Desa Ciburial sebagai Sarana Promosi Wisata - Rahman, Yanuar (Visualita Jurnal Online Desain Komunikasi Visual, 2023)
Tourist villages as part of Indonesia's tourism sector hold a significant position and value. After facing the challenges of the global pandemic, the tourism industry is now gradually recovering, with tourist villages gaining attention for offering authentic and unique travel experiences compared to conventional destinations. One of the tourist villages experiencing a resurgence is Desa Ciburial, located in the northern region of Kabupaten Bandung, West Java Province. It presents diverse potential tourist destinations, including cultural experiences, natural attractions, culinary delights, and homestays. The main issue faced by Desa Ciburial is the decline in tourist visits due to the pandemic. Therefore, smart and effective promotion strategies are necessary to support growth and increase visitor numbers. Social media, particularly Instagram, is acknowledged as a powerful promotional platform due to its ability to share visual content. The research employs a qualitative descriptive method, involving data collection and interpretation from the Instagram account @desaciburial. The data analyzed consists of visual content such as photos, videos, and infographics/illustrations published by the account. The analysis categorizes the types of content and message conveyed to form strategies for enhancing the promotion of the tourist village. This research contributes to understanding the importance of effective promotion in increasing visits to Desa Ciburial. By identifying the types of content and messages that successfully capture tourists' attention, it is hoped that the study can assist in formulating more effective and impactful promotional strategies to boost the quantity of visits to Desa Ciburial.